ANALISIS PENGARUH TRANSFER PRICING DAN STRUKTUR KEPEMILIKAN TERHADAP TAX AVOIDANCE - Dematria Pringgabayu; Imas Purnamasari; Budi Supriatono Purnomo (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to examine the influence of transfer pricing variables, institutional ownership, and managerial ownership to tax avoidance either partially or simultaneously. This research method used is quantitative method by using descriptive explanative method. This study uses secondary data in the form of financial statements of manufacturing companies listed on the Indonesia Stock Exchange period 2017 to 2021 with a population of 33 companies and 132 samples. The analytical method used to measure the effect of transfer pricing, ownership structure to tax avoidance is multiple linear regressions. The results show that transfer pricing does not affect tax avoidance because it does not have significant implications (no effect) because the potential taxable income (although shifted from one to another agency) was still within the same jurisdiction of taxation. Meanwhile, the result of the research shows that the variable of institutional ownership has a negative effect on tax avoidance because the large concentration of institutional ownership will influence the aggressive tax policy and the managerial ownership does not affect the tax avoidance because the company in Indonesia has a very small managerial ownership of about 5%.